ANALISIS EKONOMI RUMAH TANGGA PETANI NELAYAN DALAM MENDUKUNG STRATEGI PENGHIDUPAN BERKELANJUTAN KAWASAN PANTAI BARON KABUPATEN GUNUNGKIDUL - Liana Fatma Leslie Pratiwi; Suhatmini Haryastuti (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2011)
This study aims to determine the outpouring of fishermen-farmer's work time in earning a living income contributionoffishing as a livelihoodstrategydone byfishermen-farmercomparedto the total householdincome, improvement of poverty rate and welfare of fishermen-farmer 's household, and livelihood sustainability viewed from the availability of natural resources. Basic method used was descriptive analytical method Sampling method used was snowball sampling. The number of sample used was 60 respondentsfrom three kinds offishermen status (owner of ship, fishermen laborer andfishing groudfishermen). Outpouring of work time was analyzed by t test using one sample t test. The changeli of poverty rate and welfare offishermen-farmer's family were calculated by poverty concept of Sayogyo, BPS, GSR (Good Service Ratio) and NTPRP (Farmers Household Income Exchange), then analyzed by t test using paired two sample for means. The income contribution offarm andfishing as a livelihood strategy was described by the percentage of contribution to the total household income. Futhermore, the natural resources sustainanbility was measured by Ecological Footprint concept. The results showed that fishermen-farmer's household had achieved of sustainable livelihoodTujuan penelitian ini adalah mengetahui curahan waktu kerja petani nelayan dalam mencari nafkah, kontribusi pendapatan usaha nelayan sebagai strategi penghidupan yang dilakukan petani nelayan terhadap total pendapatan rumah tangga, perubahan tingkat kemiskinan dan kesejahteraan rumah tangga petani nelayan, dan keberlanjutan penghidupan dilihat dari sumber daya alam yang tersedia. Metode dasar yang digunakan adalah metode deskriptif analitis. Pengambilan sampel menggunakan metode snowball sampling. Jumlah sampel yang digunakan dalam penelitian ini sebanyak 60 responden dari berbagai status nelayan (pemilik kapal, buruh nelayan, dan nelayan darat). Curahan waktu kerja petani nelayan dianalisis dengan uji t menggunakan one sample t test, perubahan tingkat kemiskinan dan kesejahteraan rumah tangga dihitung dengan menggunakan konsep kemiskinan Sayogyo, BPS, GSR (Good Service Ratio) dan NTPRP (Nilai Tukar Pendapatan Rumah Tangga Petani) yang dianalisis dengan uji t menggunakan paired two sample for means, kontribusi pendapatan usaha nelayan sebagai strategi penghidupan diketahui dengan menghitung persentase kontribusinya terhadap total pendapatan rumah tangga, dan keberlanjutan sumber daya alam dihitung menggunakan konsep Ecological Footprint. Hasil penelitian menunjukkan bahwa rumah tangga petani nelayan telah mencapai penghidupan berkelanjutan.